The effect of using the bubble mental map on learning the skills of preparation and receiving transmissions in female students volleyball - زينة حسن أ.د. نجلاء عباس (الرياضة المعاصرة)
Several cognitive strategies, methods, methods, and teaching aids have emerged that help the teacher achieve the goal they want. Among these learning methods are mind maps, which are one of the means that contribute to stabilizing the information of the learner, especially the game of volleyball, which includes many basic skills. The basic skills of volleyball, as the study aims to identify the effect of using the bubble mental map in learning some basic skills of volleyball for students, and also included two assumptions, namely 1- There are no statistically significant differences between the pre and post tests of the experimental and the control groups in some basic skills of female students volleyball 2- There are no statistically significant differences between the experimental and control groups in the post test in some basic skills of female students volleyball ,Consequently, the researcher concluded that there is a clear effect of the bullous mental map used during the lesson, through the results obtained by the researcher from the difference between the results of the tribal and posttest tests on the students, and therefore the study recommends the need to use the mental map during the educational process because of the educational effect of the lesson.